Optimization of electro discharge critical process parameters in tungsten carbide drilling using L9 Taguchi approach. (2021) - Kumar Vates, Umesh; Jee Kanu, Nand; Gupta, Eva; Kumar Singh, Gyanendra; Prakash Sharma, Bhupendra; Pandey, Vivek
Abstract: Industries are further demanding improved and automated unconventional technologies for metal removal in difficult -to-machine materials. Furthermore, super finishing, dimensional accuracy, low wastage, and quick machining action play an important role as far as customer demand is concern. The electro discharge drilling (EDD) process combines conventional drilling and thermos physical spark machining, which is also called hybrid machining. Tungsten carbide (WC) is selected as a work material for drilling through hybrid machining in the present investigation. The WC is an extremely hard and difficult to machine material composite. Industries are using such type of hexagonal structural materials for specific purposes, industrial components, abrasives and cutting tools, etc. In the present investigation, the L9 Taguchi design of experiments has been adapted for hybrid drilling on tungsten carbide (WC) with the influence of spark erosion oil (SEO-25). Discharge current, pulse-on time, pulse-off time, and copper tool rotational speed were selected as critical influencing parameters to investigate material removal rate (MRR), tool wear rate (TWR), and surface roughness (Ra).